The impact of seed-policy reforms and intellectual property rights on crop productivity in India - Kolady, Deepthi Elizabeth; Spielman, David J.; Cavalieri, Anthony J.; International Maize and Wheat Improvement Center; International Livestock Research Institute; International Rice Research Institute; WorldFish (International Food Policy Research Institute, 2014)
Numerous studies have shown that the liberalization of seed market policies and stronger legal protection of intellectual property rights (IPR) can stimulate private investment in agriculture, especially crop genetic improvement. However, few studies have examined whether this translates into increased agricultural productivity. This study1 explores this question in the context of India, where policy reforms during the late 1980s opened the door to private investment in the seed market, and where more recent reforms have afforded private innovators with stronger IPR protections over plant varieties.